PHARMACOLOGICAL APPRAISAL OF CUMINUM CYMINUM L. IN DYSMENORRHOEA: AN AYURVEDIC APPROACH IN CONSIDERATION OF CURRENT EVIDENCES - Dilip Jani; *Jasmine Gujarathi (International Journal of Ayurveda and Pharma Research, 2017)
The demand of personalized medication has grown to leaps and bounds since last few years. Ayurveda, the oldest system of medicine, emphasized on such personalized medication by analyzing the personal health status of individual through different assessment criteria. Cuminum cyminum L. called as Jeeraka in Sanskrit and Jeera in Hindi, is one of the herb which was used since many centuries for various ailments. Traditionally the herb is well-known for its action in various alimentary diseases like, indigestion, diarrhea, gynecological diseases, etc. This herb is also screened for various pharmacological activities like antibacterial, anticancer, antiulcer and others. The condition of painful menstruation is affecting more than half of young adolescent girl population. The current article is an effort to establish the mode of action of Cuminum cyminum L in terms of Ayurveda pathogenesis as well as contemporary science. Various pathogenic pathways of Dysmenorrhoea according to Ayurveda are discussed with conclusion of using Jeeraka in dysmenorrhoea under which particular pathogenesis. Such comparison will help to establish personalized medicine for other diseases and this may be a novel approach towards same.